Morphometric and the genetic variations in wild populations of oreochromis mossambicus and its potential hybrids in Limpopo Province, South Africa - Mashele, Mahlatse Fiona (My University, 2025)
The current study presented a comprehensive analysis of O. mossambicus and its possible hybrids inhabiting four localities, with a focus on morphometric and genetic assessments to identify species and hybridization patterns. The morphometric analysis used discriminant analysis and principle component analysis to class the tilapia species and investigate which morphometric features contributed the most in differentiating among the four tilapia species. Genetic verification was conducted using mitochondrial DNA and nuclear DNA markers. The mitochondrial COI gene was amplified using the FishF primer, while the 5S gene for nuclear DNA was analyzed using the 5SA primer and analyzed using Bayesian inference and maximum likelihood. The morphometric analysis revealed the presence of four distinct species, Oreochromis mossambicus, Oreochromis niloticus, Coptodon rendalli, and T. sparrmanii alongside evidence of hybridization between O. mossambicus and O. niloticus. The genetic data corroborated the morphometric findings, confirming the existence of O. mossambicus, O. niloticus, their hybrids and T sparrmanii, however, Coptodon rendalli failed to amplify, due to poor amplicon quality. Hybridization occurring between the native O. mossambicus and the introduced O. niloticus showed a significant risk to the genetic diversity of O. mossambicus, as the introgression of genetic material from the exotic O. niloticus could lead to the erosion of unique genetic traits in the native species. The results also showed that the tilapia species in the study had the same nucleotides for the 5S gene and differentiation was only observed in the Non-transcribed spacer (NTS) part of the gene. The findings also highlighted the need for management strategies to mitigate the impact of hybridization and preserve the genetic integrity of O. mossambicus, noting significant differences between wild and cultured O. mossambicus species due to one mutation from a sample in Flagboshielo Dam. Conservation efforts should focus on monitoring hybridization rates and implementing measures to control the spread of O. niloticus within native ranges of native Oreochromis species. The genetic dilution of O. mossambicus by the exotic O. niloticus emphasizes the urgent need for conservation actions to prevent the loss of genetic diversity in the native tilapia population.
Thesis (M. Sc. Agriculture (Aquaculture)) -- University of Limpopo, 2025
Keywords: Mossambicus; Hybrid inhibiting four localities; Morphometric and the genetic assessment; Periphyton; Mozambique tillapia; Cichlidae